Nepetin Attenuates Atopic Dermatitis in HaCaT Cells and BALB/c Mice through MyD88-MKK3/6-Akt Signaling - Gong, Guowei; Ganesan, Kumar; Zheng, Yuzhong; Xiao, Jian; Dong, Tina Tingxia; Tsim, Karl Wah Keung (Current Medicinal Chemistry, 2025)
IntroductionNepetin is a type of O-methylated flavone (6-hydroxy luteolin) and has been found in many herbal medicines that exhibit various pharmacological properties, including anti-inflammatory responses. Here, we aimed to investigate the efficacy of nepetin in attenuating inflammatory responses in cultured keratinocytes and 2,4-dinitrochlorobenzene (DNCB)-induced atopic dermatitis (AD) in BALB/c mice.MethodsVarious assay methods including cell viability, flow cytometry, fluorometry, confocal microscopy, western blot, ELISA techniques, staining methods, score and scratch frequency assessment, etc. were employed to explore the mechanisms.ResultsLPS-treated keratinocytes showed a significant increase in inflammatory mediators (iNOS, COX-2, PGES2, and NO) and cytokines (IL-1β, IL-6, and TNF-α) in a dose-dependent manner. Treatment with nepetin prevented LPS-induced cell death and inhibited inflammatory mediators and the production of cytokines in cultured keratinocytes. This inhibition was achieved by nepetin, which inhibited LPS-induced ROS production and the translocation of NF-κB in the cultures, thereby inhibiting the generation of inflammatory mediators and/or cytokines. In a mouse model of AD, treatment with nepetin reduced skin inflammation symptoms in a dose-dependent manner, as evidenced by the significant reduction of inflammation-related cytokines, skin lesions, and behavior scores.ConclusionBased on the present in vitro and in vivo study, nepetin is the safest bioactive compound with potential therapeutic applications for AD-related skin lesions and adverse skin reactions.
Keywords: Nepetin